2016
DOI: 10.4209/aaqr.2015.02.0078
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Emissions of Particulate Matter from Intensive Pig Production at a Large Farm in North China

Abstract: Particulate matter (PM) pollution from pig farms is of increasing environmental concern due to the rapid development of intensively managed pig farms worldwide. However, information on this topic is scarce in China to date. Therefore a two-year study to monitor the dynamics of total suspended particles (TSP) and particulate matter with diameter less than 10 µm (PM 10 ) and their soluble ions was conducted at an industrial pig farm near Beijing. In total, two fattening pig houses were sampled during three fatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It is an important topic since NH3 emitted from animal barns is an essential precursor for SIA formation and SIAs account for a significant fraction of atmospheric PM2.5 (up to 80%). However, the IC quantification data from both studies (Yang et al, 2011;Xu et al, 2016) showed that NO3and SO4 2were not fully neutralized by NH4 + in PM. Thus, part of NO3and SO4 2could originate from minerals or nitrification and should not be included in the calculation of SIA mass in swine barns.…”
Section: Soluble Ionsmentioning
confidence: 92%
See 3 more Smart Citations
“…It is an important topic since NH3 emitted from animal barns is an essential precursor for SIA formation and SIAs account for a significant fraction of atmospheric PM2.5 (up to 80%). However, the IC quantification data from both studies (Yang et al, 2011;Xu et al, 2016) showed that NO3and SO4 2were not fully neutralized by NH4 + in PM. Thus, part of NO3and SO4 2could originate from minerals or nitrification and should not be included in the calculation of SIA mass in swine barns.…”
Section: Soluble Ionsmentioning
confidence: 92%
“… PM concentrations show significant seasonality (Predicala et al, 2001;Schmidt et al, 2002;Zhu et al, 2005;Jerez et al, 2009;Yao et al, 2010;Peters, et al, 2012;Basinas et al, 2013;Xu et al, 2016;Yang et al, 2015;Shang et al, 2020), with generally the highest concentrations occurring in winter and the lowest concentrations in summer. Such seasonality is believed to be related to ventilation rates (Predicala et al, 2001;Yang et al, 2015).…”
Section: Pm Mass Concentrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rising demand for food, especially for livestock products, has elicited great concerns over their negative environmental impacts [1][2][3]. In different parts of the world, animal production is highly concentrated, and intensive large-scale animal husbandry operations have expanded rapidly [4,5]. Not only are there more animals in the farms, but the farms themselves are becoming more specialized, consequently increasing their environmental load; this includes their contamination load upon soil and water, and their gaseous load upon air [5,6].…”
Section: Introductionmentioning
confidence: 99%